Prevalence of smear positivity, hiv co-infection, trend and treatment outcome among tuberculosis patients accessing care at faith alive foundation, Jos, Nigeria - HA, Agbo; ME, Banwat; M, Isichei; Chris, Isichei (Archives of Community Medicine and Public Health, 2021)
Background: Tuberculosis (TB) in the African sub-region, is still a public health problem, heightened by its synergy with HIV. Sputum smear positivity which is diagnostic indicator often gives a lower prevalence of the disease that may be give a false burden of the disease thus leading to varied treatment outcomes that may add to the vicious cycle of the magnitude of the disease. Thus, the prevalence of sputum positivity and co-infection with HIV; trend and treatment outcomes of TB were assessed. Methods: Secondary data of TB patients from 2012 (commencement of TB care at this centre) - 2018 at Faith Alive Foundation Jos, a renowned faith-based hospital with approximately with a large monthly patient turn-out rate. Software SPSS version 18 was used for data analysis. Results: Females adults were more affected; prevalence of sputum positivity/HIV co-infection were 15.1% (14% in adult; 1.1% in children) / 62.0% (57.4% in adults; 4.6% in children) respectively. The 7-year trend spiked in year 2015 and 2017, with an observed downward pattern in 2018 in all the ages. Cure after treatment was 6.3% (5.7% in adults and 0.6% in children). Conclusion: Efforts will need to be put into TB diagnosis considering the low sensitivity of sputum smear microscopy in instituting treatment. TB is still a leading opportunistic infection in persons infected with HIV.